Water-based tourism dynamics: spatial and temporal characterization in three coral reefs from Bahía Culebra, North Pacific of Costa Rica - López Romero, Gabriela Mercedes (2026)
Introduction: Coral reefs are essential ecosystems for tourism-based economies worldwide, offering ecological, social and economic benefits. However, increasing on-water activities represent a risk to reef health. In Culebra Bay, there is limited understanding of how on-water tourism interacts with the coral reefs of the area. Objective: To characterize the spatial and temporal distribution of on-water tourism interactions around coral reefs sites in Culebra Bay. Methods: Direct observations were conducted twice a month from April 2021 to April 2022, at three coastal coral reefs to document the number of interactions and users, the types of activities and watercraft involved, and the duration of each interaction. A Kruskal-Wallis test was applied to evaluate differences across sites, and the U Mann-Withney test for compare tourist seasons (peak and off-season). Additionally, a Correspondence Analysis (CA) was used to explore the relationship between activities and sites. Results: We recorded 2,437 interactions involving 6 728 users, and identified ten tourism-related activities. The spatial distribution of tourism interactions was heterogeneous among sites, with the highest volume of interactions, activities, and users concentrated at Jícaro reef. The activities involving watercraft-based activities were dominant, representing 93% of all interactions. Also, the recorded activities were different by site: Blanca reef was mainly linked to non-motorized tours, while Virador reef was primarily used for transit. We found no statistical differences in the volume of users, the temporal distribution of interactions and its duration between seasons. Conclusion: Aquatic tourism in Bahía Culebra was concentrated at Jícaro reef and dominated by motorized activities. This pattern may pose potential environmental risks for reef resilience.